2018
DOI: 10.26687/archnet-ijar.v12i3.1658
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Factors Affecting Social Interaction in the Parks of Baghdad City, Iraq

Abstract: Since the war in 2003, Baghdad has suffered from different aspects of political, administration, economic ethnic, sectarian, etc. that led to the loss of lives, social capital, destruction of Iraqi infrastructure and important buildings, increased crisis aggravation between different ethnics, as well as the disappearance and destruction of many Baghdad’s open spaces, parks, and recreational places. This paper addresses the issue of social interaction in Baghdad city, resulting from the lack of open spaces, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Furthermore, students from different ethnicities showed different levels of individual outdoor informal study and outdoor group formal activities in Malaysian universities. These findings contributed to the evidence from existing literature found that individuals' experience in nearby small parks could vary n=based on their socio-demographic backgrounds (Zheng et al, 2011), such as age (Abd El-Aziz, 2015), gender (Salih and Ismail, 2018b), and education (Mertens et al, 2019). However, an experimental study conducted in the USA reported homogenous responses across demographic variables (Cohen et al, 2014).…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, students from different ethnicities showed different levels of individual outdoor informal study and outdoor group formal activities in Malaysian universities. These findings contributed to the evidence from existing literature found that individuals' experience in nearby small parks could vary n=based on their socio-demographic backgrounds (Zheng et al, 2011), such as age (Abd El-Aziz, 2015), gender (Salih and Ismail, 2018b), and education (Mertens et al, 2019). However, an experimental study conducted in the USA reported homogenous responses across demographic variables (Cohen et al, 2014).…”
Section: Discussionsupporting
confidence: 57%
“…Lack of quality public open spaces and parks means the residents of Baghdad had fewer places for their daily activities and social interactions (JAU et al, 2011). Long T-concrete walls, roadblocks, and checkpoints have interrupted movements along the arterial roads in the Baghdad city, causing the residents to prefer to shop, work, and socialize within their neighborhood (JAU et al, 2011;Salih and Ismail, 2018b). The recent economic, political, and urban conditions in the city have disabled the provision of large green open spaces.…”
Section: Pocket Parksmentioning
confidence: 99%
“…Pocket parks can be defined as low-cost, small green open spaces for various activities and benefits. Pockets reflect a new innovative tool by unifying the efforts of local communities and the responsible authorities in the design and maintenance processes (Peschardt and Stigsdotter, 2014;Salih and Ismail, 2018b). According to several recent studies, small and green open spaces have a critical role in promoting socialization, relaxation, recreation, and various health benefits for users of different genders, ages, ethnicities, and cultures Ismail, 2018a, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the current study only included four demographic characteristics, including gender, ethnicity, education status, and university. The evidence from the existing studies con rmed that users' factors such as age, income level, and occupation also in uence their activities and use of nearby open space 10,49,50,51 . However, it was not possible within the current study to include more items as the additional items could increase the burden on the respondents.…”
Section: Discussionmentioning
confidence: 96%